Quantile-based heterogeneous effects of nuclear energy and political stability on the environment in highly nuclear energy-consuming and politically stable countries - Kartal, Mustafa Tevfik; Depren, Serpil Kilic; Ayhan, Fatih; Ulussever, Talat (ELSEVIER SCI LTD, 2024)
The study analyzes the effects of nuclear energy and political stability (PS) on environmental degradation. For this aim, the study uses carbon dioxide (CO2) emissions as the environmental degradation indicator, considers nuclear energy consumption (NEC) and political risk index (PRI) as explanatory variables, uses data between 1991/Q1 and 2021/Q4, and investigates eight highly politically stable countries in this way. Also, the study performs novel quantile-on-quantile regression and Granger causality-in-quantiles models as the fundamental models and applies the quantile regression model for robustness. The results reveal that (i) NEC has a mainly curbing effect on CO2 emissions at higher levels of NEC and is beneficial for Finland, Switzerland, Canada, Netherlands, and United Kingdom; (ii) PS has a generally decreasing effect on CO2 emissions at higher levels of PS and is effective in Finland, Canada, and Germany; (iii) NEC and PS have a causal mainly effects on CO2 emissions in the countries; (iv) the robustness of the results is verified through alternative approach. Overall, there are dependencies from NEC and PS to CO2 emissions and the effects of both NEC and PS on CO2 emissions vary across countries and quantiles. Hence, the results highlight the heterogeneous effects of NEC and PS on CO2 emissions and underline the significance of quantile and country-based analyses for better empirical examination. Various policy caveats are discussed based on the fact that Finland and Canada can benefit from both NEC and PS in decreasing CO2 emissions, whereas Sweden and the USA cannot, and the remaining countries have mixed results. {GRAPHIACAL ABSTRACT}
Keywords: Nuclear energy; Political stability; CO (2); Quantile-based models; CO2 EMISSIONS; RENEWABLE ENERGY; ECONOMIC-GROWTH; KUZNETS CURVE; PRICE; Energy & Fuels; Engineering